1999
DOI: 10.1007/s11745-999-0359-7
|View full text |Cite
|
Sign up to set email alerts
|

Changes in body composition in mice during feeding and withdrawal of conjugated linoleic acid

Abstract: Two experiments were conducted. In Experiment 1, 8-wk-old mice were fed control diet or diet supplemented with 0.5% conjugated linoleic acid (CLA) to study the effect of CLA on body composition (CLA: 40.8-41.1% c-9,t-11 isomer, 43.5-44.9% t-10,c-12 isomer). The data for CLA-fed mice vs. controls described parallel but significantly distinct responses for both absolute and relative changes in body fat mass (reduced in CLA-fed mice) and for relative changes in whole body protein and whole body water (both of whi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

15
169
1
9

Year Published

2000
2000
2020
2020

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 285 publications
(198 citation statements)
references
References 7 publications
15
169
1
9
Order By: Relevance
“…It was later found that synthetic CLA had several beneficial effects such as anticarcinogenesis [3,4], antiatherogene [5,6], decrease of body fat [7,8], and regulation of immunological reactions [9,10].…”
Section: Introductionmentioning
confidence: 99%
“…It was later found that synthetic CLA had several beneficial effects such as anticarcinogenesis [3,4], antiatherogene [5,6], decrease of body fat [7,8], and regulation of immunological reactions [9,10].…”
Section: Introductionmentioning
confidence: 99%
“…They are found in edible foods, such as ruminants meats, pasteurized dairy products, and processed cheeses (Ha et al, 1989;Chin et al, 1992). CLA exhibits several beneficial effects, such as a protective effect against cancer and heart disease (Ip et al, 1991;Ip et al, 1994;Lee et al, 1994), and reduced body fat mass in experimental animals (Park et al, 1997;West et al, 1997;Park et al, 1999). Furthermore, Houseknecht et al showed that CLA is capable of improving glucose tolerance in hyperglycemic Zucker rats (Houseknecht et al, 1998).…”
Section: Introductionmentioning
confidence: 99%
“…In other studies, CLA increased body protein concentration or lean body percentage without modification of absolute amounts, in mice [13][14][15], rats [16] and humans [17,18]. It has also been shown to increase lean mass, protein levels and muscle mass in mice [19][20][21], rats [22], pigs [23] and humans [1,24,25]. The discrepancies in the results, even within a specific species, suggest that several factors such as genotype, age, diet, or physical activity may interfere with CLA effects.…”
Section: Introductionmentioning
confidence: 81%
“…Mixtures of conjugated linoleic acid isomers (CLA) were initially shown to reduce the percentage of whole body fat and/or the mass of fat pads, in mice [1] and then in rats, hamsters, pigs and hu-CLA feeding had no effect on these parameters in mice [4], rats [5][6][7][8][9][10], hamsters [9,11] and humans [12]. In other studies, CLA increased body protein concentration or lean body percentage without modification of absolute amounts, in mice [13][14][15], rats [16] and humans [17,18].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation